Ideology in a socio-semiotic linguistic theory e0003 - Lukin, Annabelle (Universidad Nacional del Litoral, 2021)
This article is the translation of Chapter 3 of the book War and Its Ideologies: A Social-Semiotic Theory and Description. Springer Digital Publication, 2019. Annabelle Lukin is Associate Professor in the Department of Linguistics at Macquaire University, Sydney, Australia. His research interests include the study of language in politics, media, health, and literature. She was a disciple of M.A.K. Halliday and Ruqaiya Hasan. In 2019 he published War and its Ideologies: A Social-Semiotic Theory and Description, a book based on 15 years of research on how language legitimizes some forms of violence while stigmatizing others.